Cytotoxicity and anti-Leishmania amazonensis activity of Citrus sinensis leaf extracts. (1st January 2017) - Garcia, Andreza R.; Amaral, Ana Claudia F.; Azevedo, Mariana M. B.; Corte-Real, Suzana; Lopes, Rosana C.; Alviano, Celuta S.; Pinheiro, Anderson S.; Vermelho, Alane B.; Rodrigues, Igor A.
Abstract: Context: Leishmania amazonensis is the main agent of diffuse cutaneous leishmaniasis, a disease characterized by lesional polymorphism and the commitment of skin surface. Previous reports demonstrated that the Citrus genus possess antimicrobial activity. Objective: This study evaluated the anti- L. amazonensis activity of Citrus sinensis (L.) Osbeck (Rutaceae) extracts. Materials and methods: Citrus sinensis dried leaves were subjected to maceration with hexane (CH), ethyl acetate (CEA), dichloromethane/ethanol (CD/Et – 1:1) or ethanol/water (CEt/W – 7:3). Leishmania amazonensis promastigotes were treated with C. sinensis extracts (1–525 μg/mL) for 120 h at 27 °C. Ultrastructure alterations of treated parasites were evaluated by transmission electron microscopy. Cytotoxicity of the extracts was assessed on RAW 264.7 and J774.G8 macrophages after 48-h treatment at 37 °C using the tetrazolium assay. In addition, Leishmania -infected macrophages were treated with CH and CD/Et (10–80 μg/mL). Results: CH, CD/Et and CEA displayed antileishmanial activity with 50% inhibitory activity (IC50 ) of 25.91 ± 4.87, 54.23 ± 3.78 and 62.74 ± 5.04 μg/mL, respectively. Parasites treated with CD/Et (131.2 μg/mL) presented severe alterations including mitochondrial swelling, lipid body formation and intense cytoplasmic vacuolization. CH and CD/Et demonstrated cytotoxic effects similar to that of amphotericin B in the anti-amastigote assays (SI of 2.16, 1.98 and 1.35, respectively). Triterpene amyrins were the main substances in CH and CD/Et extracts. In addition, 80 μg/mL of CD/Et reduced the number of intracellular amastigotes and the percentage of infected macrophages in 63% and 36%, respectively. Conclusion: The results presented here highlight C. sinensis as a promising source of antileishmanial agents.